Limites e possibilidades do negócio jurídico processual em matéria tributária - Gaspar, Flávia Soraya Maia Bandeira Lima (Universidade Federal Rural do Semi-Árido, 2019)
The Legal Bargain Process is not new in Brazilian law, but with the advent of the Civil Procedure Code of 2015, the typical Procedural Juridical Bargain were extended and the so-called Atypical Procedural Jurisdictions, disciplined in article 190 of the respective legal diploma. In the quest for speed of procedure, active participation of the parties to the process and a narrowing relationship between the tax and the taxpayer, a study on this instrument is relevant with the objective of identifying the limits and possibilities of the application of this institute, noting whether the treasury may appear as a party to that procedural agreement, due to the unavailability of the public interest that permeates the tax matter. It is also important to verify if there is a standardization of this institute in the tax area. For that, a bibliographic research was carried out, analyzing articles from periodicals, dissertations, theses, doctrine, pertinent legislation, as well as articles of opinion, institutional sites, in the search to answer the problematic: can the Public Treasury conduct legal bargain in tax matters? And what would be its limits and scope? Therefore, this article intends to analyze the limits and possibilities of the Legal Bargain Procedure to be celebrated in tax matters.
Artigo Acadêmico
Keywords: Negócio jurídico processual em matéria tributária; Interesse público; Transação tributária; Bargain legal in tax matters; Public interest; Tax transaction; CIENCIAS SOCIAIS APLICADAS::DIREITO